Effects of position of semi-circular body on melting of a novel B4C/ RT44HC PCM nanocomposite in a closed space - Gurgenc, Ezgi; Gur, Muhammed; Cosanay, Hakan; Gurgenc, Turan; Öztop, Hakan Fehmi (Elsevier, 2025)
This study focuses on optimizing the thermal performance of a novel Boron Carbide (B4C) enhanced RT44HC phase change material (PCM) nanocomposite by analyzing the effects of different semi-circular partition placements within a closed cavity. The primary objective is to determine how the position of these adiabatic bodies influences the melting behavior, thermal conductivity, and energy storage capacity of the PCM. Through detailed computational modeling using the finite volume method and experimental validation, the research reveals that incorporating B4C nanoparticles significantly improves thermal performance, achieving up to a 69.65 % increase in thermal conductivity and a 19.68 % enhancement in energy storage capacity compared to pure PCM. The findings contribute to the field of advanced thermal energy storage and management by presenting a robust strategy for optimizing heat transfer in PCM systems, with potential applications in sustainable building design, electronic cooling, and energy-efficient technologies.
Keywords: Natural convection; Nano enhanced PCM; Computational fluid dynamics; Cavity; Semi circle partitions